The Anatomic Variations of the Circle of Willis in Preterm-at-Term and Term-Born Infants: An MR Angiography Study at 3T - Malamateniou, C.; Adams, M.E.; Srinivasan, L.; Allsop, J.M.; Counsell, S.J.; Cowan, F.M.; Hajnal, J.V.; Rutherford, M.A. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: It has been shown that the brain of a preterm infant develops differently from that of a term infant, but little is known about the neonatal cerebrovascular anatomy. Our aims were to establish reference data for the prevalence of the anatomic variations of the neonatal circle of Willis (CoW) and to explore the effect of prematurity, MR imaging abnormality, vascular-related abnormality, laterality, and sex on these findings. MATERIALS AND METHODS: We scanned 103 infants with an optimized MR angiography (MRA) protocol. Images were analyzed for different variations of the CoW, and results were compared for the following: 1) preterm-at-term and term-born infants, 2) infants with normal and abnormal MR imaging, 3) infants with and without a vascular-related abnormality, 4) boys and girls, and 5) left- and right-sided occurrence. RESULTS: The most common anatomic variation was absence/hypoplasia of the posterior communicating artery. Preterm infants at term had a higher prevalence of a complete CoW and a lower prevalence of anatomic variations compared with term-born infants; this finding was significant for the anterior cerebral artery (P = .02). There was increased prevalence of variations of the major cerebral arteries in those infants with vascular-related abnormalities, statistically significant for the posterior cerebral artery (P = .004). There was no statistically significant difference between boys and girls and left/right variations. CONCLUSIONS: Prematurity is associated with more complete CoWs and fewer anatomic variations. In vascular-related abnormalities, more variations involved major arterial segments, but fewer variations occurred in the communicating arteries. Overall reference values of the variations match those of the general adult population.